DAMPAK TEKNIK SADAP SPIRAL TERHADAP PENERIMAAN PETANI KARET DI KABUPATEN TANJUNG JABUNG TIMUR - Rizki Gemala Busyra (Universitas Batangahari Jambi, 2021)
One of the way to increase rubber productivity and its production, is by focusing to recommended tapping techniques. In East Tanjung Jabung Regency although the recommended rubber tapping technique (i.e. spiral tapping technique) had been socialized, but there were still many rubber farmers who done a non-spiral tapping techniques. This will certainly affect the amount of latex production and the rubber plants life duration. The low amount of rubber production will lead to a low number of sales, so it will have an impact on the low revenue of rubber farmers. The purpose of this study was to find out the impact of the application of spiral tapping techniques on rubber crops toward farmer. The results showed that simultaneously the independent variables had a Significant effect on the Farmer revenues. Partially, rubber production and rubber prices had showed a significant effect on farmer’s revenues, while the age of crops and tapping techniques, had no significant effect on the farmer’s revenues. Although the variables of tapping techniques did not significantly effect to the farmer revenue but it gave the higher revenue than the other tapping techniques.